Endocytic Clathrin-coated Pit Formation Is Independent of Receptor Internalization Signal Levels - Santini, Francesca (The American Society for Cell Biology, 1998)
The mechanisms responsible for coated pit formation in cells remain unknown, but indirect evidence has argued both for and against a critical role of receptor cytoplasmic domains in the process. If the endocytic motifs of receptors are responsible for recruiting AP2 to the plasma membrane, thereby driving coated pit formation, then the level of constitutively internalized receptors at the membrane would be expected to govern the steady-state level of coated pits in cells. Here we directly test this hypothesis for broad classes of receptors containing three distinct constitutive internalization signals. Chimeric proteins consisting of an integral membrane reporter protein (Tac) coupled to cytoplasmic domains bearing tyrosine-, di-leucine-, or acidic cluster/casein kinase II-based internalization signals were overexpressed to levels that saturated the internalization pathway. Quantitative confocal immunofluorescence microscopy indicated that the number of plasma membrane clathrin-coated pits and the concentration of their structural components were invariant when comparing cells expressing saturating levels of the chimeric receptors to nonexpressing cells or to cells expressing only the Tac reporter lacking cytoplasmic internalization signals. Biochemical analysis showed that the distribution of coat proteins between assembled coated pits and soluble pools was also not altered by receptor overexpression. Finally, the cellular localizations of AP2 and AP1 were similarly unaffected. These results provide a clear indication that receptor endocytic signals do not determine coated pit levels by directly recruiting AP2 molecules. Rather, the findings support a model in which coated pit formation proceeds through recruitment and activation of AP2, likely through a limited number of regulated docking sites that act independently of endocytic signals.